SENSITIZATION TO STREPTOCOCCUS PYOGENES AT CHILDREN OF EARLY AND PRESCHOOL AGE WITH RECURRENT RESPIRATORY INFECTIONS — PREDICTORS OF RHEUMATIC PATHOLOGY - E. V. Shabaldina (Sankt-Peterburg : NIIÈM imeni Pastera, 2015)
Streptococcus pyogenes is the reason of rheumatism and a post-streptococcal glomerulonephritis. Primary colonization of mucosal with this microorganism develops in the period of early ontogenesis. It was confirmed that at a carriage of this microorganism children at them activate immunopathological reactions. Clinic and immune features of the children with recurrent respiratory infections of early and preschool age having the immune response to S. pyogenes were studied. Position of risk of formation of rheumatic diseases at these children was studied. 771 children, in an age interval of 2–6 years are examined. Immune and clinical indicators in two groups of the children having the immune response to S. pyogenes (n = 306) and not having it (n = 465) were analyzed. It was shown that in group of the children with immune response to S. pyogenes were authentically higher: point of an hereditary predisposition, expressiveness of placental insufficiency and a fetal hypoxia during the real pregnancy, and in the post-natal period degree of a thymomegaly, a pharyngeal lymphoid ring hypertrophy, skin manifestations of food allergy on the first year of life, the frequency of sharp respiratory infections within one year — in comparison with control. The group of the children having the immune response to S. pyogenes had a high level in a nasal secret of TNFα, IL-4, IFNα, and in blood — ASL-O, ASG, RF, CRP and immunoglobulin E. It was shown that at the children with a sensitization to S. pyogenes were lowered in peripheral blood: the general leukocytes, lymphocytes, T-lymphocytes (CD3 positive), T-helpery (CD3 and CD4 positive), an immunoregulatory index (the relation of CD4 of positive lymphocytes to CD8 to positive lymphocytes), phagocytosis (in test with nitro blue tetrazolium chloride — NBT) and immunoglobulin A — in comparison with control. The atopic immune response to S. pyogenes, S. pneumoniae, S. aureus, P. vulgaris, K. pneumoniae, H. influenzae took place in the main group. The average logarithmic cultivation titer of these microorganisms was also authentically higher at children of the main group. The conducted research showed that hyper productive immune reactions mainly on humoral type which can provide induction of rheumatic pathology are associated with the immune response to S. pyogenes; and detection of IgG antibodies to S. pyogenes can be screening for identification of group of risk on formation of rheumatic diseases among children with recurrent respiratory infections and a pharyngeal lymphoid ring hypertrophy.